101k views
3 votes
Rewrite 5 to the second power + (4-2)-6 using grouping symbols to give a different answer.show how to evaluate

User Keely
by
5.3k points

1 Answer

4 votes

Rewrite the expression by using the grouping symbols.


\begin{gathered} 5*3(4-2)-6=5*3(2)-6 \\ =15\cdot(2)-6 \\ =30-6 \\ =24 \end{gathered}

So answer after simplication is 24.

User Jacob Horbulyk
by
4.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.